Nuevos datos paleontológicos (Graptolithina), bioestratigráficos y paleogeográficos del área de Santa Victoria, Cordillera Oriental, Argentina (Ameghiniana, 2014)
A new graptolite assemblage is described from the Acoite Formation in the Santa Victoria area (Salta Province), located in the northeastern sector of the Argentinian Eastern Cordillera. Five species, Baltograptus deflexus (Elles y Wood), B. turgidus (Lee), B. kunnnngensi« (Ni), B. iondingensis (Li) and B. boliuianus (Finney y Branisa) are described, and their stratigraphic range is discussed. The assemblage is referred to the Baltograptus deflexus Zone, and assigned an Early Arerugian age (equivalent to Bendigonian of the Australian zonation). The paleogeographic affinities of this assemblage are thought to he with the western area of the Eastern Cordillera. This would suggest él close relationship between both sectors of the basin and would confirm an intermediate paleolatitudi nal loca tion for the transitional zone of northwestern Argentina during Early Arenigian times.